2018
DOI: 10.1139/cjss-2017-0001
|View full text |Cite
|
Sign up to set email alerts
|

Nitrous oxide and carbon dioxide emissions from surface and subsurface drip irrigated tomato fields

Abstract: Irrigation practices change the soil moisture in agricultural fields and influence emissions of greenhouse gases (GHG). A 2 yr field study was conducted to assess carbon dioxide (CO2) and nitrous oxide (N2O) emissions from surface and subsurface drip irrigated tomato (Solanum lycopersicum L.) fields on a loamy sand in southern Ontario. Surface and subsurface drip irrigation are common irrigation practices used by tomato growers in southern Ontario. The N2O fluxes were generally ≤50 μg N2O-N m−2 h−1, with mean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 19 publications
1
8
1
Order By: Relevance
“…Only two studies reported a significant decrease in CO 2 emissions with lower amount of irrigated water applied or with a change in irrigation strategies. Studies that compared surface drip irrigation and subsurface drip irrigation systems in Canada found negligible effect on CO 2 emissions [67]. Similar non-significant findings were reported by Maris et al [78] in Spain when they evaluated the effect of surface drip and subsurface drip irrigation on the CO 2 emissions.…”
Section: Effects Of Irrigation On Co 2 Emissionssupporting
confidence: 73%
See 1 more Smart Citation
“…Only two studies reported a significant decrease in CO 2 emissions with lower amount of irrigated water applied or with a change in irrigation strategies. Studies that compared surface drip irrigation and subsurface drip irrigation systems in Canada found negligible effect on CO 2 emissions [67]. Similar non-significant findings were reported by Maris et al [78] in Spain when they evaluated the effect of surface drip and subsurface drip irrigation on the CO 2 emissions.…”
Section: Effects Of Irrigation On Co 2 Emissionssupporting
confidence: 73%
“…They found that subsurface drip irrigation can mitigate N 2 O emissions compared to drip irrigation. However, another study showed a negligible impact on N 2 O emissions when tomatoes were irrigated comparing surface drip and subsurface drip irrigation systems [67]. A cotton study in China showed that drip irrigation, which uses less water than furrow irrigation could significantly decrease N 2 O emissions when combined with certain management practices.…”
Section: Effects Of Irrigation On N 2 O Emissionsmentioning
confidence: 99%
“…All the benefits plus the reduced N 2 O emissions in this study make SDI preferable to the DI. Edwards et al [13] did not find significant difference in N 2 O emissions between SDI and DI from a tomato field because the drip tape in their study was buried at a much shallower depth (15 cm depth below the surface) compared to the ~50 cm depth in our study. They did illustrate that higher surface soil moisture from DI resulted in significantly higher seasonal CO 2 emissions than SDI.…”
Section: Mitigation Of N 2 O Emission Through Irrigation and Ferticontrasting
confidence: 72%
“…Wei et al [12] reported subsurface watering to saturate subsurface soil at 15-50 cm reduced N 2 O emissions in soil boxes. Subsurface drip at 15 cm soil depth in a tomato field, however, did not reduce emissions [13]. In a cotton field with raised beds, Bronson et al [14] reported that N 2 O emissions ranged from 0.1-0.54%, 0.15-1.1%, and <0.1% of added N fertilizer for furrow, sprinkler, and subsurface drip irrigation (to 22-28 cm depth) systems, respectively.…”
Section: Introductionmentioning
confidence: 95%
“…Guo et al [20] also found that cumulative CO 2 emissions on the irrigation pipes was larger than that between irrigation pipes. Edwards et al [31] measured emissions from surface and subsurface drip (drip tape buried to 15 cm soil depth) irrigated tomato field for two years with significantly higher cumulative emissions from surface drip than subsurface drip, but they attributed the difference to sampling time temperature difference and concluded that the irrigation methods did not have a direct impact on CO 2 emissions. Fares et al [32] measured CO 2 emissions from different irrigation levels [75% (deficit), 100%, and 125% (excess) of reference crop evapotranspiration] using surface drip irrigation system and found no statistical differences among the irrigation levels.…”
Section: Cumulative Co 2 Emissionsmentioning
confidence: 99%